2020
DOI: 10.1108/lhtn-10-2019-0071
|View full text |Cite
|
Sign up to set email alerts
|

What is the relationship between marketing of library sources and services and social media? A literature review paper

Abstract: Purpose The aim of this study is to determine the relationship between social media and libraries in terms of marketing. The present research is to find out the factors and impact as well as the issues related to libraries and marketing using social media. This study will give massive information regarding social media use for the marketing of library sources and services. Design/methodology/approach This study so far has been taken into account to review all the related literature of social media and librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…In such a setting, social media enable countless interactions between producers and consumers, facilitating order management, supplier management, product and service advertising, sourcing of ideas for improving products and services, and so on, while lowering the cost of their use (Anwar & Zhiwei, 2020). Furthermore, social media could increase consumers' confidence in making safe purchasing decisions thanks to positive experiences of consumers who speak favorably about the attributes of a product they consumed and their recommendation to other consumers (Baum et al, 2018;Tuten & Perotti, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a setting, social media enable countless interactions between producers and consumers, facilitating order management, supplier management, product and service advertising, sourcing of ideas for improving products and services, and so on, while lowering the cost of their use (Anwar & Zhiwei, 2020). Furthermore, social media could increase consumers' confidence in making safe purchasing decisions thanks to positive experiences of consumers who speak favorably about the attributes of a product they consumed and their recommendation to other consumers (Baum et al, 2018;Tuten & Perotti, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Social media is defined as technological means used to generate communications and transactions that allow the development of business activities to be used through the customer network and promote the creation of value (Andzulis et al, 2012;Anwar & Zhiwei, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Their research unveiled several findings, including a prevalence of studies conducted in areas with limited professional development (PD) resources, underscoring the economic benefits of utilizing social media, and a greater tendency among tech-savvy librarians to adopt social media for PD. Through a comprehensive examination of the literature on social media and library marketing, Anwar and Zhiwei (2020) showed that despite the challenges and issues libraries face when adopting social media for promoting their resources and services, it remains the most effective tool for the job. Mamdapur et al (2022) undertook a bibliometric analysis of 1,208 articles on social media and libraries collected from the Scopus database spanning 2002 to 2021.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Keterlibatan kepuasan pelanggan digunakan untuk mengetahui seberapa besar kontribusinya dalam meningkatkan minat pembelian pelanggan. Jika konsumen tertarik pada produk atau layanan yang diberikan, mereka cenderung lebih tertarik untuk melakukan pembelian (Alhakimi and Albashiri, 2023); Anwar, and Zhiwei (2023). Minat beli mengacu pada kecenderungan konsumen untuk melakukan berbagai langkah sebelum melakukan pembelian.…”
Section: Pendahuluanunclassified